Drivers of microbial community structure in forest soils - Lladó, Salvador; López-Mondéjar, Rubén; Baldrian, Petr (Applied microbiology and biotechnology, 2018)
Forests are essential biomes for global biogeochemical cycles, and belowground microorganisms have a key role in providing relevant ecosystem services. To predict the effects of environmental changes on these ecosystem services requires a comprehensive understanding of how biotic and abiotic factors drive the composition of microbial communities in soil. However, microorganisms are not homogeneously distributed in complex environments such as soil, with different features affecting microbes at different extent depending on the niche they occupy. Indeed, this spatial heterogeneity hampers the extrapolation of microbial diversity study results from particular habitats to the ecosystem level, even if the resolution of the more recent studies has increased significantly after the standardization of high-throughput sequencing techniques. The present work intends to give a comprehensive view of the knowledge accumulated until date defining the more important drivers determining the structure of forest soil microbial communities from fine to continental scales.
Keywords: mikrobiota; lesy; Drivers; Microbial diversity; Bacteria; půda; Soil; Microbiota; Soil Microbiology; Community structure; Forests; Forest; půdní mikrobiologie; ekosystém; Ecosystem